ANALISA KERUSAKAN PADA PINTU ELEVATOR UNIT LP 01 DI TERMINAL INTERNASIONAL BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - Wibowo, Imam Haryadi; Novarizki Adityanto Nursin, Muhammad Samudera; Haqim, Maulana Nurul; Aufi Syabani, M. Khaidar; Dwi Argo, Anfendra Lerry Agus; Yulia, Candra Dewi (Program Studi Teknik Mekanikal Bandar Udara, 2023)
The background of this research journal is the fact that the duration ofOJT (On The Job Training) Cadets of Airport Mechanical Engineeringat I Gusti Ngurah Rai airport, which is for approximately 5 months. Thisactivity aims to increase the comfort of elevator users at I Gusti NgurahRai Bali airport, damage to the elevator door can reduce passengercomfort or passenger ratings. This journal will also support the repairor maintenance of elevators around the scope of the IndonesianAviation Polytechnic Curug dormitory. Elevator doors play animportant role in ensuring smooth and safe operations at airports.Elevator door damage can cause serious disruption to passengermobility and goods delivery. Therefore, this study aims to analyze thedamage to the elevator doors at I Gusti Ngurah Rai Airport, Bali. Inmaking the journal, the authors conducted research using qualitativemethods to find problems with elevator doors based on direct events atI Gusti Ngurah Rai International Airport in Bali. The method in thisjournal uses 2 data, namely primary data and supporting data. Primarydata is obtained from direct observation in the field so that data on thedamage that occurs to the elevator door is obtained. Supporting data isobtained by searching various references on the internet, journals, andmanuals. Meanwhile, in our data collection method we usedobservation, interviews and literature study. The solution to preventdamage to the elevator door is to carry out maintenance as follows, check the elevator door, check the movement of the door when openingand closing, check the door hanger once a week, the condition of thedoor hanger makes the door tilt or not. If the condition of the door hanger makes thedoor tilt, immediately make repairs to the door hangerto prevent the door from getting out of its way and carry outmaintenance and cleaning of the eccentric roller within 1 week andcheck whether the elevator door is tight or not when it is closed, if it isnot tight, immediately set the door elevators. These findings highlightthe need for greater attention to maintenance and maintenance ofelevator doors at airports. The airport management company mustensure that routine maintenance systems are carried out regularly andthat trained and qualified technicians are assigned to carry outinspection, repair and replacement of damaged components. Thisresearch provides a better understanding of elevator door damage at IGusti Ngurah Rai Airport Bali and provides a solid basis for improvingthe efficiency and reliability of the elevator system. It is hoped that thesefindings will be useful for related parties in developing a more effectivemaintenance strategy and reducing unwanted downtime at the elevatordoors at the airport.